Identification and functional analysis of Git3 G protein-coupled receptors in Ganoderma boninense PER71 - Khairunnisa Hanisah Mohd Daud; Mohd Faizal Abu Bakar; Izwan Bharudin; Shazilah Kamaruddin; Huai, Doris Xia Quay; Farah Diba Abu Bakar; Abdul Munir Abdul Murad (Penerbit Universiti Kebangsaan Malaysia, 2024)
G protein-coupled receptors (GPCRs) are integral components of eukaryotic heterotrimeric G proteins, playing crucial roles in detecting extracellular signals and initiating the activity of signaling proteins within cells to activate cellular responses to these signals. The objectives of this study are to identify and characterize the function of Git3, a Class III GPCR protein, in the oil palm pathogen Ganoderma boninense. To identify the potential genes encoded for GPCR in this fungus, intensive data mining on the genome and transcriptome data has been carried out. A total of six classes of GPCRs have been identified. These include Class II pheromone detectors, Class III carbon detectors, Class IV nitrogen detectors, Class VII proteins similar to glycosyltransferase, Class VIII proteins similar to hemolysin, and Class X protein receptors. Among these, the Class III protein Git3, postulated to be involved in glucose sensing and fungal pathogenicity, was selected for gene knockdown using RNA interference (RNAi). A plasmid, designated pUChph-GIT3, was constructed, to target git3 silencing by incorporating a hygromycin resistance gene cassette and antisense sequences of git3. Transformation of G. boninense PER71 with pUChph-GIT3 produced five potential Δgit3 gene-silenced mutants. PCR analysis confirmed the integration of the RNAi expression cassette into the fungal genome. Quantitative PCR (qPCR) analysis revealed significant reductions in git3 expression in three G. boninense mutants, M42, M66, and M5 by 47%, 23%, and 13%, respectively. The Disease Severity Index (DSI) indicated slower disease progression in oil palm plantlets infected with Δgit3 mutants compared to those infected with wild-type G. boninense PER71. In conclusion, this study successfully isolated and characterized the git3 GPCR from G. boninense and demonstrated that it might play a role during the early stages of infection, as the mutants were able to slow the progression of infection in oil palm plantlets.